Antarctic minke whales find ice gaps along the ice edge in foraging grounds of the Indo-Pacific sector (60° E and 140° E) of the Southern Ocean - Konishi, Kenji; Isoda, Tatsuya; Bando, Takeharu; Minamikawa, Shingo; Kleivane, Lars (Polar Biology, 2020)
Keywords: Sørishavet; forskning; hvaler; krill; marin biologi; næring

Environmental influences on the at-sea behaviour of a major consumer, Mirounga leonina, in a rapidly changing environment - McIntyre, Trevor; Bornemann, Horst; de Bruyn, P J Nico; Reisinger, Ryan R; Steinhage, Daniel; Márquez, Maria E I; Bester, Marthán N; Plötz, Joachim (Polar Research, 2014)
Understanding the distribution and foraging ecology of major consumers within pelagic systems, specifically in relation to physical parameters, can be important for the management of bentho-pelagic systems undergoing rapid change associated with global climate change and other anthropogenic disturbances such as fishing (i.e., the Antarctic Peninsula and Scotia Sea). We tracked 11 adult male southern elephant seals (Mirounga leonina), during their five-month post-moult foraging migrations from King George Island (Isla 25 de Mayo), northern Antarctic Peninsula, using tags capable of recording and transmitting behavioural data and in situ temperature and salinity data. Seals foraged mostly within the Weddell–Scotia Confluence, while a few foraged along the western Antarctic Peninsula shelf of the Bellingshausen Sea. Mixed model outputs suggest that the at-sea behaviour of seals was associated with a number of environmental parameters, especially seafloor depth, sea-ice concentrations and the temperature structure of the water column. Seals increased dive bottom times and travelled at slower speeds in shallower areas and areas with increased sea-ice concentrations. Changes in dive depth and durations, as well as relative amount of time spent during the bottom phases of dives, were observed in relation to differences in overall temperature gradient, likely as a response to vertical changes in prey distribution associated with temperature stratification in the water column. Our results illustrate the likely complex influences of bathymetry, hydrography and sea ice on the behaviour of male southern elephant seals in a changing environment and highlight the need for region-specific approaches to studying environmental influences on behaviour. Keywords: Southern elephant seals; foraging ecology; satellite-relay data loggers; King George Island; Isla 25 de Mayo; at-sea behaviour.
Keywords: Sørishavet; batymetri; havis; klimaendringer; miljø; næring; seler; sjøis

Foraging economics and performance of polar and subpolar Atlantic seabirds - Croxall, John P; Briggs, Dirk R (Polar Research, 1991)
Keywords: Antarktis; fugler; næring; ornitologi; pingviner; zoologi; økologi

Occurrence of polar seabirds at sea in relation to prey concentrations and oceanographic factors - Hunt Jr, George L (Polar Research, 1991)
Keywords: Antarktis; næring; ornitologi; oseanografi; polarområdene; sjøfugler; økosystemer

The pelagic distribution of marine birds in a heterogeneous environment - Hunt Jr, George L. (Polar Research, 1990)
Keywords: Antarktis; fugler; marin ornitologi; næring; polarområdene

Næringer i hvalfangstens grenseland - Ringstad, Jan Erik (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1990)
Keywords: Christen Christensen; Sørishavet; historie; hvalfangst; hvalkokerier; hvalolje; næring; patenter; pelagisk; økonomi

Hvorfor gikk det så greitt? Om nedleggelsen av hvalfangstnæringen i Vestfold - Vik, Kjell (Vestfoldminne, 1984)
Keywords: Sørishavet; Vestfold; historie; hvalfangere; hvalfangstindustri; hvalindustri; næring; pelagisk; sjøfolk; økonomi

Noen problemer i den moderne hvalfangsts historie - Tønnessen, Johan Nicolay (Vestfold-minne, 1964)
Keywords: Carl Anton Larsen; Henrik Johan Bull; Svend Foyn; Sørishavet; historie; hvalfangstindustri; hvalfangstselskaper; hvalindustri; næring; pelagisk; polareksspedisjoner; økonomi

Den moderne hvalfangstens kausalproblemer - Johnsen, Arne Odd (Historisk tidsskrift)
Keywords: Sørishavet; historie; hvalfangstindustri; hvalindustri; næring; pelagisk; økonomi